2000
DOI: 10.1021/jf000916p
|View full text |Cite
|
Sign up to set email alerts
|

Production, Purification, and Properties of an Endoglucanase Produced by the HyphomyceteChalara(Syn.Thielaviopsis)paradoxaCH32

Abstract: The hyphomycete Chalara (syn. Thielaviopsis) paradoxa produces endoglucanase activity during the late trophophase. The low molecular mass (35 kDa) endoglucanase purified from cultured broths works optimally at 37 degrees C and pH 5.0. The enzyme inactivates at pH below 3.0 and also at temperatures of 50 degrees C or higher, but it is stable at lower temperatures, including refrigeration temperature and freezing. The enzyme is inhibited by detergents, by EDTA, and by the divalent cations Hg(2+) and Ag(2+). It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 42 publications
(45 reference statements)
5
18
1
Order By: Relevance
“…Our results have high similarity to those found for Catharanthus roseus (Sanwal 1999). Saha (2004) and Lucas et al (2001) reported that the activities of enzymes produced by Mucor circinelloides and Chalara paradoxa were greatly enhanced when incubated with Co 2+ and Mn 2+ .…”
Section: Effect Of Substrate Concentration: Determination Of Km and Vmaxsupporting
confidence: 86%
“…Our results have high similarity to those found for Catharanthus roseus (Sanwal 1999). Saha (2004) and Lucas et al (2001) reported that the activities of enzymes produced by Mucor circinelloides and Chalara paradoxa were greatly enhanced when incubated with Co 2+ and Mn 2+ .…”
Section: Effect Of Substrate Concentration: Determination Of Km and Vmaxsupporting
confidence: 86%
“…As the temperature increased cas et al [41] for Chalara paradoxa. This is possibly due to binding of Hg 2+ with thiol groups and interaction with carboxyl or imidazol groups of amino acids [41]. Activation by Co 2+ and Mn 2+ is similar to results of Saha [37] from M. circineloides.…”
Section: Effect Of Temperature On Activity Of Cellulasementioning
confidence: 97%
“…Bakare et al [38] reported an inhibitory effect of EDTA to the activities of cellulase from wild type of Pseudomonas fluorescens. According to Saha, [36] and Lucas et al [40] Co 2+ and Mn 2+ activate the enzyme that from Mucor circinelloides and Chalara paradoxa respectively.…”
Section: Effect Of Activators and Inhibitorsmentioning
confidence: 99%